2015
DOI: 10.4067/s0718-381x2015000100004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antibacterial Effect of 2% Chlorhexidine Against Enterococcus faecalis in Dentin Previously Irrigated with 5% Sodium Hypochlorite

Abstract: In vitro antibacterial effect of 2% chlorhexidine against Enterococcus faecalis in dentin previously irrigated with 5% sodium hypochlorite. Int. J. Odontostomat., 9(1):25-29, 2015. ABSTRACT:The aim of this study was to observe whether the antibacterial effect of 2% chlorhexidine against Enterococcus faecalis in dentine is altered by previous irrigation with 5% sodium hypochlorite. Dentin discs were prepared with different irrigation protocols: group 1, immersed in 2% CHX for 25 min; group 2 immersed in 5% NaOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…The most significant antimicrobial effects are achieved when using gutta-percha with chlorhexidine, indicating the greatest reduction in bacterial cultures after contact with this substance. Study results indicated that chlorhexidine is effective against Enterococcus faecalis, a notion supported by numerous other studies demonstrating both the in vitro and in vivo effectiveness of this aspect [40][41][42][43][44][45][46][47]. Furthermore, chlorhexidine exhibits biocidal activity against Gram-positive bacteria, and, if the minimum inhibitory concentration (MIC) is maintained, it can also inhibit Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 74%
“…The most significant antimicrobial effects are achieved when using gutta-percha with chlorhexidine, indicating the greatest reduction in bacterial cultures after contact with this substance. Study results indicated that chlorhexidine is effective against Enterococcus faecalis, a notion supported by numerous other studies demonstrating both the in vitro and in vivo effectiveness of this aspect [40][41][42][43][44][45][46][47]. Furthermore, chlorhexidine exhibits biocidal activity against Gram-positive bacteria, and, if the minimum inhibitory concentration (MIC) is maintained, it can also inhibit Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 74%
“…Vem se mostrando como possível substituto do NaOCl por resultar uma menor toxicidade, ter ação antimicrobiana contra espécies resistentes ao NaOCl, menor tensão superficial e por demonstrar ação residual após a interação com a dentina, fenômeno conhecido como substantividade. No entanto, a CHX não apresenta um potencial de degradação dos tecidos orgânicos, uma importante condição das soluções químicas que são usadas ao longo da preparação dos canais, sendo associada com o NaOCl por preencherem as condições de uma solução irrigante ideal na endodontia (EcheverrI & Alderete, 2015).…”
Section: Reação Entre a Clorexidina (Chx) E O Hipoclorito De Sódio (Naocl)unclassified